2019
DOI: 10.1158/1541-7786.mcr-18-1121
|View full text |Cite
|
Sign up to set email alerts
|

GSK2801, a BAZ2/BRD9 Bromodomain Inhibitor, Synergizes with BET Inhibitors to Induce Apoptosis in Triple-Negative Breast Cancer

Abstract: Screening of an inhibitor library targeting kinases and epigenetic regulators identified several molecules having antiproliferative synergy with extraterminal domain (BET) bromodomain (BD) inhibitors (JQ1, OTX015) in triplenegative breast cancer (TNBC). GSK2801, an inhibitor of BAZ2A/B BDs, of the imitation switch chromatin remodeling complexes, and BRD9, of the SWI/SNF complex, demonstrated synergy independent of BRD4 control of P-TEFbmediated pause-release of RNA polymerase II. GSK2801 or RNAi knockdown of B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 57 publications
2
51
0
Order By: Relevance
“…3 ). Antiproliferative synergy has also been observed in triple negative breast cancer when the bromodomains of BRD9 and bromodomain adjacent zinc finger BAZ2A are inhibited concurrently [ 129 ]. In addition, there appears to be a connection between splicing factor protein SF3B1 mutations and BRD9 degradation in cancers like myeloid leukemia, lymphoid leukemia, and uveal melanoma [ 130 ].…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%
“…3 ). Antiproliferative synergy has also been observed in triple negative breast cancer when the bromodomains of BRD9 and bromodomain adjacent zinc finger BAZ2A are inhibited concurrently [ 129 ]. In addition, there appears to be a connection between splicing factor protein SF3B1 mutations and BRD9 degradation in cancers like myeloid leukemia, lymphoid leukemia, and uveal melanoma [ 130 ].…”
Section: Gbaf and Its Subunits In Mammalian Diseasementioning
confidence: 99%
“…In BRCA1-deficient breast cancer, BET inhibitors induce DNA damage and kill cancer cells by elevating cellular oxidative stress [31]. In TNBC, BET inhibitors exert anti-tumor functions by blocking cell proliferation, inducing cell apoptosis and inhibiting angiogenesis [5,7,[32][33][34]. Moreover, BET inhibitors have been reported to enhance the effect of immunotherapy by suppressing transcriptional expression of MYC in TNBC [35].…”
Section: Discussionmentioning
confidence: 99%
“…By constructing the cell lines selected for acquired resistance to BET inhibition, they clarified the mechanisms of BETi resistance in TNBC [6]. Recently, several studies reported that BET inhibitors combined with other agents such as BAZ2/BRD9 inhibitor GSK2801, Bcl-XL inhibitor and vitamin C exert synergistic effect in ducing TNBC cells apoptosis [7][8][9]. Moreover, currently several clinical trials with BETi have been approved for cancer treatment.…”
mentioning
confidence: 99%
“…Targeting Brd9 is possible and in vivo active inhibitors are available [112]. It has been attempted in vitro in rhabdoid tumours [113] and in vivo in other entities [114].…”
Section: The Epigenetic Consequences Of Smarcb1 Alterationsmentioning
confidence: 99%